STUDI METODE PERKUATAN LERENG MENGGUNAKAN GEOMAT, SHOTCRETE, DAN SOIL NAILING (Studi Kasus: Lereng Spillway Bendungan Sadarwana Paket II Subang) - Putra, Sahal Priyono; Rochim, Abdul; Sumirin, Sumirin (Wahana Teknik Sipil: Jurnal Pengembangan Teknik Sipil, 2023)
The landslide of the upper slope in the excavation work of the spillway SadawarnaDam Package II Subang occurred after rain, precisely at the STA location from0+500 to 0+520. The purpose of the study was to compare soil reinforcement on theprevious spillway slope using geomat and shotcrete with soil reinforcement usingsoil nailing. Based on soil data the spillway slope consists of two types of slopes, theupper slope consists of CL (BS:03) while the lower consists of ML (BS:04). Theshear strength parameters C and Phi of both slope soils are quite high. Using PlaxisV.21, Slope/W and Seep/W, with C and Phi the slopes were found to be stable.However, in reality there was a landslide on the upper slope. Therefore, backanalysis was performed by lowering the strength parameters of the top soil adjacentto the slope until the landslide was realized. The reinforcement used on the twoslopes was different, the upper slope used geomat while the lower slope usedshotcrete, then the geomat was changed to soil nailing. Two seasonal models wereapplied to all reinforcements. The results showed that the factor of safety valuesfrom the back analysis modeling in the wet season using geomat and shotcrete wereless than 1 (Unstable). However, reinforcement using soil nailing has a SafetyFactor higher than 1.5. Based on these results, soil nailing can be a solution tominimize landslides on the spillway slope.